Systemic Weaknesses of Budget Management in anglophone Africa - Lienert, Ian (International Monetary Fund, 2001)
This paper examines the merits of the British budget management system that was inherited in Anglophone African countries and which has changed substantially in the United Kingdom since the 1960s. It considers whether the disappointing budgetary performance in Africa is due to weaknesses in the inherited British system, other external influences, or domestic developments. It finds that all three factors have played a role in the widespread problems with budget management systems. Reforms in institutional arrangements are needed, especially in budget execution. Technical reforms will be ineffective unless there are concomitant changes to enhance accountability, improve governance, and increase compliance